PENGARUH PERTUMBUHAN EKONOMI, SUKU BUNGA DAN PAJAK TERHADAP INVESTASI ASING LANGSUNG - Dewi, Putu Kartika; Triaryati, Nyoman (E-Jurnal Manajemen, 2015)
Foreign investors (Foreign Direct Investment) assist Indonesia in developing the nation. FDI funding adjunct a financial development in Indonesia. This study aimed is to determine the effect of economic growth, interest rates and tax as a independend variable on foreign direct investment as a dependend variable. This research data source is time series secondary data within 13 years period of time (2001-2013). This study uses multiple regression analysis technique. This research foundithat economic growth has a significant positive effect on foreign direct investment and the tax rate has a significant negative effect on foreign direct investment.
Keywords: profitability; credit risk; liquidity risk; operational risk